Correction: Troncoso et al. Incentive Policies for Scientific Publications in the State Universities of Chile. Publications 2022, 10, 20 - Elizabeth Troncoso; Francisco Ganga-Contreras; Margarita Briceño (Publications, 2022)
Missing Acknowledgments [...]